Clouds enhance Greenland ice sheet meltwater runoff - K. Van Tricht (Nature Portfolio, 2016)
Clouds play a pivotal role in the energy and mass balance of the Greenland ice sheet, thereby affecting its contribution to global sea-level rise. Here, using a combination of observations and model simulations, the authors show that clouds enhance Greenland ice sheet meltwater runoff by more than 30%.